Logistics reverse lamp post-consumer fluorescente case study: storage system in a educational institution - Cestari, William; Martins, Carlos Humberto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Fluorescent bulbs are considered hazardous waste and should have their post-consumer appropriate destination. Public and private companies are working to reverse logistics in order to maximize the use of resources and improve the corporate image, creating economic, social, environmental value, and meet current legislation. This study aims to find out how the storage of post-consumption fluorescent lamps is performed in a higher education institution, located in the city of Maringa-PR, making sure it is stored in accordance with the theories found to hazardous waste storage and reverse logistics is being held as the National Policy on Solid Waste (PNRS - Law 12.305 / 2010) in compliance with the law. The research involved literature on articles, newspapers, magazines, books and internet that deal with the subject. With regard to the case study, addition of in situ observation, it was found the amount of post-consumer fluorescent lamps located in the warehouses of the analyzed institution. Improvement proposals are presented in the current storage process, using theoretical framework. With the proposed, the storage process standardization and reverse logistics social, environmental and economic benefits will be evident.